2016
DOI: 10.1074/jbc.m115.685750
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of X-Box-binding Protein One (XBP1) by Hepatocyte Nuclear Factor 4α (HNF4Α) Is Vital to Beta-cell Function

Abstract: The transcription factor, X-box-binding protein-1 (XBP1), controls the development and maintenance of the endoplasmic reticulum (ER) in multiple secretory cell lineages. We show here that Hepatocyte Nuclear Factor 4␣ (HNF4␣) directly induces XBP1 expression. Mutations in HNF4␣ cause Mature-Onset Diabetes of the Young I (MODYI), a subset of diabetes characterized by diminished GSIS. In mouse models, cell lines, and ex vivo islets, using dominant negative and human-disease-allele point mutants or knock-out and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 57 publications
1
25
0
3
Order By: Relevance
“…Quantitative real-time PCR (qRT-PCR) was performed to assess the quantity of genomic sequences immunoprecipitated by either preimmune control or HNF4␣ antiserum, as well as a 1:10 dilution of the cell extract prior to immunoprecipitation (input). Two predicted HNF4␣ binding sites (41) were probed in addition to an intronic control region with no predicted HNF4␣ binding sites nearby.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) was performed to assess the quantity of genomic sequences immunoprecipitated by either preimmune control or HNF4␣ antiserum, as well as a 1:10 dilution of the cell extract prior to immunoprecipitation (input). Two predicted HNF4␣ binding sites (41) were probed in addition to an intronic control region with no predicted HNF4␣ binding sites nearby.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that transcription factors other than ATF6 induce Xbp1 expression. For example, HNF1α and HNF4α were found to induce Xbp1 expression in pancreatic β-cells [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…We observed for the first time that the increase in expression and activity of HNF4α during differentiation led to the transcriptional upregulation of two of the three primary ER stress mediators: XBP1 and ATF6. HNF4α, which is considered to be important in the development of endodermal organs, is also required for continued maintenance of XBP1 in differentiated, adult cells . Analysis of a publicly available ChIP‐Sequencing dataset (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE23436) indicated that the only gene that showed promoter enrichment for HNF4α in the differentiated Caco‐2 cells that was common to the GO terms ER stress, cell differentiation, and autophagy (please see below for further discussions on autophagy) was XBP1 .…”
Section: Discussionmentioning
confidence: 99%